Selective Enrichment of Omega-3 Fatty Acids in Oils by Phospholipase A1. - Tushar Ranjan Moharana; Avinesh R Byreddy; Munish Puri; Colin Barrow; Nalam Madhusudhana Rao (PLoS ONE)
Omega fatty acids are recognized as key nutrients for healthier ageing. Lipases are used to release ω-3 fatty acids from oils for preparing enriched ω-3 fatty acid supplements. However, use of lipases in enrichment of ω-3 fatty acids is limited due to their insufficient specificity for ω-3 fatty acids. In this study use of phospholipase A1 (PLA1), which possesses both sn-1 specific activity on phospholipids and lipase activity, was explored for hydrolysis of ω-3 fatty acids from anchovy oil. Substrate specificity of PLA1 from Thermomyces lenuginosus was initially tested with synthetic p-nitrophenyl esters along with a lipase from Bacillus subtilis (BSL), as a lipase control. Gas chromatographic characterization of the hydrolysate obtained upon treatment of anchovy oil with these enzymes indicated a selective retention of ω-3 fatty acids in the triglyceride fraction by PLA1 and not by BSL. 13C NMR spectroscopy based position analysis of fatty acids in enzyme treated and untreated samples indicated that PLA1 preferably retained ω-3 fatty acids in oil, while saturated fatty acids were hydrolysed irrespective of their position. Hydrolysis of structured triglyceride,1,3-dioleoyl-2-palmitoylglycerol, suggested that both the enzymes hydrolyse the fatty acids at both the positions. The observed discrimination against ω-3 fatty acids by PLA1 appears to be due to its fatty acid selectivity rather than positional specificity. These studies suggest that PLA1 could be used as a potential enzyme for selective concentrationof ω-3 fatty acids.